Interpreting Myocardial Enzymatic Biomarkers in the Setting of Acute Myocardial Infraction AMI - Khawla A. Kasar; Maha H. Al-Bahrani; Ahmed A. Mohsin (Journal of Techniques)
The rates of morbidity and mortality for acute myocardial infarction (AMI) have been rising quickly in the last few years. In the systemic circulatory loop, the heart normally pumps blood to the body's extremities. Cardiovascular disease, however, results from any heart function problem. The most fatal diseases in the world are known to be those involving the cardiovascular system. Over the past decade, biochemical marker testing are an important step in the diagnosis, and management of heart failure and in lowering one's risk of developing cardiovascular disease. Early diagnosis is paramount to choosing a clear and effective treatment strategy. Cardiac biomarkers are another effective method for classifying myocardial injury. The myocardial enzymatic biomarkers, also known as myocardial necrosis biomarkers, were among the various biomarkers that were initially studied. This review aims to allow for appropriate management steps to be initiated and more efficient and effective utilization of healthcare resources.